2011
DOI: 10.1152/ajprenal.00615.2010
|View full text |Cite
|
Sign up to set email alerts
|

Protein complexes that control renal epithelial polarity

Abstract: Establishment of epithelial apicobasal polarity is crucial for proper kidney development and function. In recent years, there have been important advances in our understanding of the factors that mediate the initiation of apicobasal polarization. Key among these are the polarity complexes that are evolutionarily conserved from simple organisms to humans. Three of these complexes are discussed in this review: the Crumbs complex, the Par complex, and the Scribble complex. The apical Crumbs complex consists of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
98
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(98 citation statements)
references
References 177 publications
(244 reference statements)
0
98
0
Order By: Relevance
“…We finally compared the distribution of ABP components in Nectin-3 +/-and Nectin-3 -/-auditory epithelia. Three major ABP complexes, namely, the apical Crumbs complex consisting of Crumbs3 (Crb3), Pals1 (Mpp5 -Mouse Genome Informatics) and Pals1-associated tight junction protein (Patj), the Par complex consisting of Par-3, Par-6 (Pard6 -Mouse Genome Informatics) and atypical protein kinase C (aPKC), and the lateral Scribble complex consisting of Scribble, discs large (Dlg1) and Lgl, are essential for epithelial ABP formation (Pieczynski and Margolis, 2011). In the surface view of the Nectin-3 +/-auditory epithelium, the immunofluorescence signal for Pals1 was concentrated at the phalloidin-negative apical surface of HCs, which was polarised towards the lateral side (Fig.…”
Section: Research Articlementioning
confidence: 99%
“…We finally compared the distribution of ABP components in Nectin-3 +/-and Nectin-3 -/-auditory epithelia. Three major ABP complexes, namely, the apical Crumbs complex consisting of Crumbs3 (Crb3), Pals1 (Mpp5 -Mouse Genome Informatics) and Pals1-associated tight junction protein (Patj), the Par complex consisting of Par-3, Par-6 (Pard6 -Mouse Genome Informatics) and atypical protein kinase C (aPKC), and the lateral Scribble complex consisting of Scribble, discs large (Dlg1) and Lgl, are essential for epithelial ABP formation (Pieczynski and Margolis, 2011). In the surface view of the Nectin-3 +/-auditory epithelium, the immunofluorescence signal for Pals1 was concentrated at the phalloidin-negative apical surface of HCs, which was polarised towards the lateral side (Fig.…”
Section: Research Articlementioning
confidence: 99%
“…The Par complex (see Box 1) is a set of evolutionarily conserved intrinsic polarity proteins, consisting of Par3, Par6 and atypical protein kinase C (aPKC), which are asymmetrically distributed at the cell cortex and have important functions in the determination of cell polarity and the orientation of the mitotic spindle (Pieczynski and Margolis, 2011). The Par complex is a main determinant of polarity.…”
Section: Intrinsic and Extrinsic Polarity Cuesmentioning
confidence: 99%
“…The Par complex, consisting of Par3, Par6 and atypical protein kinase C (aPKC), localizes to the apical cortex of epithelial cells in vertebrates, the anterior cortex in the C. elegans zygote and the apical cortex in Drosophila neuroblasts (Pieczynski and Margolis, 2011). Par3 contains multiple PDZ domains and provides anchorage to assemble the Par complex at the apical-lateral border by binding Par6 and recruiting Par6-associated proteins.…”
Section: Box 1 the Par Complex And Dyneinmentioning
confidence: 99%
“…Polarity complexes include evolutionarily conserved apical complex proteins, such as the Crb complex (comprising Crbs, Pals1, Patj), the Par complex (Par3, Par6, aPKC) and basal complex proteins, such as the Scribble complex (Scribbles, Lgl, Dlg) (Assémat et al, 2008;Pieczynski and Margolis, 2011;Tepass, 2012). Previous studies have demonstrated that apical complex proteins are necessary for self-renewal of neural progenitor cells (Bultje et al, 2009;Costa et al, 2008;Kim et al, 2010), neuronal migration (Famulski et al, 2010;Solecki et al, 2006), axon determination (Chen et al, 2013;Shi et al, 2003), dendrite development (Tanabe et al, 2010), tissue polarity and neuron survival (Kim et al, 2010).…”
Section: Introductionmentioning
confidence: 99%